DETERMINATION OF EXPORT VOLUME AND HEDGING STRATEGY: A SURVEY OF EXPORTER’S TRANSACTION AT THE MAKASSAR INDUSTRIAL ESTATE (KIMA) - Abdul Rakhman (Universitas Hayam Wuruk Perbanas, 2012)
The study aims to determine factors which influence the export volume of leading commodities in SouthSulawesi and investigate which hedging strategy has been implemented by the exporters. The survey wasundertaken for 13 managers arranging 250 sales contracts in thirteen companies. They were asked todescribe what type of hedging strategy was implemented in protecting their revenue with US dollar asdenominated currency to their contract. Several literatures suggested that hedging strategy needs to consistof hedging theory, but in South Sulawesi, the international traders’ belief is in pragmatism way byrelying on money market instrument especially for interest rate orientation. Although export import activitiesfor cocoa, cement, lobster, seaweed, box and marbles used US for denomination, the respondentswere aware of Rupiah fluctuation to foreign currency which also bears transaction exposure. Multipleregression analysis was used to determine variables which affected the volume and export, while hedgingstrategy was identified using qualitative approach. It was found that the increase on cost of hedging, inflationreferences and interest rate references affected significantly the increase of the export volume, whilethe increase of US spot rate to Indonesian Rupiah did not significantly affect in reducing export volume.Most of exporters rely on hedging in money market, long forward contract to protect their transactions.